2003
DOI: 10.1074/jbc.m213231200
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Genetic Interactions of Cytosolic Malate Dehydrogenase with Other Gluconeogenic Enzymes

Abstract: A truncated form (⌬nMDH2) of yeast cytosolic malate dehydrogenase (MDH2) lacking 12 residues on the amino terminus was found to be inadequate for gluconeogenic function in vivo because the mutant enzyme fails to restore growth of a ⌬mdh2 strain on minimal medium with ethanol or acetate as the carbon source. The ⌬nMDH2 enzyme was also previously found to be refractory to the rapid glucose-induced inactivation and degradation observed for authentic MDH2. In contrast, kinetic properties measured for purified form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…However, the vacuolar degradation pathway is unlikely to utilize this system, because FBPase ubiquitination was not observed under the vacuolar degradation conditions (38). FBPase is known to interact with MDH2 under glucose starvation conditions (44). Therefore, we determined whether the degradation defect seen in the P1S-FBPase and P1S-MDH2 mutants resulted from a reduction in their interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the vacuolar degradation pathway is unlikely to utilize this system, because FBPase ubiquitination was not observed under the vacuolar degradation conditions (38). FBPase is known to interact with MDH2 under glucose starvation conditions (44). Therefore, we determined whether the degradation defect seen in the P1S-FBPase and P1S-MDH2 mutants resulted from a reduction in their interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Mu-tagenesis studies have shown that the first 12 amino acids at the N terminus in MDH2 (⌬nMDH2) are essential for degradation. More recently, an interaction between MDH2 and FBPase has been demonstrated using the yeast two-hybrid assay and surface plasmon resonance analysis (44). Again, the Nterminal 12 amino acids are important for MDH2-FBPase interaction, because FBPase interacted with ⌬nMDH2 with a much lower affinity.…”
mentioning
confidence: 99%
“…In virtue of the close physical associations between MDH2 and PCK1 (phosphoenolpyruvate carboxykinase; see Gibson and McAlister-Henn, 2003) and since the close proximity with the next enzyme within a metabolic pathway may be important to ensure direct delivery of oxaloacetate because an interaction between sequential enzymes in a given metabolic pathway is frequently cited as evidence for the possibility of ''channeling'' of intermediates within the pathway (Estojak et al 1995) this article proposes that D-lactate translocators and D-lactate dehydrogenases work together for the removal of MG from cytosol as well as for D-lactate-dependent gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that as a result of D-lactate uptake and metabolism by S. cerevisiae mitochondria, reducing equivalents were exported from the mitochondrial matrix to the cytosol in the form of malate via a novel putative D-lactate/malate carrier. Malate is converted to oxaloacetate via yeast cytosolic gluconeogenic isozyme of malate dehydrogenase (MDH2) and could become a substrate for gluconeogenesis by virtue of the close physical associations between MDH2 and PCK1 (phosphoenolpyruvate carboxykinase; see Gibson and McAlister-Henn 2003).…”
Section: Introductionmentioning
confidence: 99%
“…MDH1 is the key enzyme in the malate/aspartate shuttle, which is the dominant pathway in the liver and heart (Scholz et al, 1998), while MDH2 is known to be a key enzyme in the TCA cycle. Cytosolic MDH, mentioned as MDH2 in yeast, has been shown to work as a gluconeogenic enzyme, because it is required for the growth of yeasts on a minimal medium in the presence of gluconeogenic precursors (Gibson and McAlister-Henn, 2003).…”
Section: Introductionmentioning
confidence: 99%